1984
DOI: 10.1093/oxfordjournals.eurheartj.a061620
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic use of cibenzoline, a new class 1 antiarrhythmic agent with class 3 and 4 properties, in patients with recurrent ventricular tachycardia

Abstract: Cibenzoline is a new antiarrhythmic agent with class 1 properties, and additional class 3 and 4 effects. We treated 28 patients with drug-refractory and recurrent ventricular tachycardia with up to 700 mg/day cibenzoline for periods up to 5.5 months. Cibenzoline prevented the recurrence of ventricular tachycardia in five patients (18%). In three patients (11%) the arrhythmia may have been worsened, in 23 patients (82%) cibenzoline was ineffective. Cibenzoline increased the PR interval by 18% and the QRS durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The trough level of the plasma concentration of cibenzoline is considered to be 25-250/xg/mL. 16 In the present study, we consider that adequate plasma concentration of cibenzoline was achieved even via gastric tube administration, and the effective plasma concentration was achieved almost within the first 24 hours. After starting normal oral administration, the effective plasma concentration was also achieved.…”
Section: Discussionmentioning
confidence: 76%
“…The trough level of the plasma concentration of cibenzoline is considered to be 25-250/xg/mL. 16 In the present study, we consider that adequate plasma concentration of cibenzoline was achieved even via gastric tube administration, and the effective plasma concentration was achieved almost within the first 24 hours. After starting normal oral administration, the effective plasma concentration was also achieved.…”
Section: Discussionmentioning
confidence: 76%
“…During chronic therapy with cibenzoline (260-700 mg/day p.0.). it has been reported that the PR interval or the AH interval increased by about 15% (5,6,10,27,47,48). Indeed, Kostis et al (29) reported that the extent of these increases in PR interval was directly proportional to the plasma concentration of cibenzoline.…”
Section: Effects On the Normal Electrocardiogrammentioning
confidence: 96%
“…(4 mg/kg) or p .~. (7 or 14 mgkg per day for [8][9][10][11][12][13][14][15][16] days), had little or no effect on AH conduction time in the in situ canine heart.…”
Section: Atrioventricular Junctionmentioning
confidence: 99%
See 2 more Smart Citations